A critical perspective on the administrative approach to crime prevention: The case of labour trafficking - Malik Hanna M; Vanto Johanna; Lähteenmäki Liisa; Vatjus-Anttila Jalo; Davies Jon (Sage Publications, 2022)
Building on empirical data from Finnish enforcement agencies, we reflect on the challenges of the administrative approach to crime prevention. At the operational level, we identify explicit legal and implicit extra-legal limitations for using the administrative approach, that we call (1) ‘tunnel view’, (2) ‘structural siloes’, (3) ‘double role’, and (4) ‘blurred lines’. At the conceptual level, we consider the challenges of using the administrative approach in the context of labour trafficking. We argue that the initial set-up of the administrative approach that stresses the serious and organised crime paradigm limits understanding of the habitual and pervasive nature of labour trafficking. Nevertheless, administrative cooperation has the potential to contribute to full ‘labour justice’ as a governance framework that coordinates the efforts of public authorities and their multidimensional strategies to account for the entire labour exploitation spectrum.